Design, user experience, and usability. designing interactions : 7th International Conference, DUXU 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: designing interactions : 7th International Conference, DUXU 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available